Equivalence of Screen Versus Print Reading Comprehension Depends on Task Complexity and Proficiency. Issue 5 (4th July 2017) - Lenhard, Wolfgang; Schroeders, Ulrich; Lenhard, Alexandra
ABSTRACT: As reading and reading assessment become increasingly implemented on electronic devices, the question arises whether reading on screen is comparable with reading on paper. To examine potential differences, we studied reading processes on different proficiency and complexity levels. Specifically, we used data from the standardization sample of the German reading comprehension test ELFE II ( n = 2, 807), which assesses reading at word, sentence, and text level with separate speeded subtests. Children from grades 1 to 6 completed either a test version on paper or via computer under time constraints. In general, children in the screen condition worked faster but at the expense of accuracy. This difference was more pronounced for younger children and at the word level. Based on our results, we suggest that remedial education and interventions for younger children using computer-based approaches should likewise foster speed and accuracy in a balanced way.